Confirmation of Skywalker Hoolock Gibbon (Hoolock tianxing) in Myanmar Extends Known Geographic Range of an Endangered Primate - Pyae Phyo Aung; Ngwe Lwin; Tin Htun Aung; Thura Soe Min Htike; Carolyn Thompson; Christian Roos; Sa Myo Zaw; L. Zawng Lum; Win Naing Oo; Zung Sau; Samuel T. Turvey; Wai Zinn Thein; et al. (International Journal of Primatology, 2024)
Characterizing genetically distinct populations of primates is important for protecting biodiversity and effectively allocating conservation resources. Skywalker gibbons ( Hoolock tianxing ) were first described in 2017, with the only confirmed population consisting of 150 individuals in Mt. Gaoligong, Yunnan Province, China. Based on river geography, the distribution of the skywalker gibbon has been hypothesized to extend into Myanmar between the N’Mai Kha and Ayeyarwaddy Rivers to the west, and the Salween River (named the Thanlwin River in Myanmar and Nujiang River in China) to the east. We conducted acoustic point-count sampling surveys, collected noninvasive samples for molecular mitochondrial cytochrome b gene identification, and took photographs for morphological identification at six sites in Kachin State and three sites in Shan State to determine the presence of skywalker gibbons in predicted suitable forest areas in Myanmar. We also conducted 50 semistructured interviews with members of communities surrounding gibbon range forests to understand potential threats. In Kachin State, we audio-recorded 23 gibbon groups with group densities ranging between 0.57 and 3.6 group/km 2 . In Shan State, we audio-recorded 21 gibbon groups with group densities ranging between 0.134 and 1.0 group/km 2 . Based on genetic data obtained from skin and saliva samples, the gibbons were identified as skywalker gibbons (99.54–100% identity). Although these findings increase the species’ known population size and confirmed distribution, skywalker gibbons in Myanmar are threatened by local habitat loss, degradation, and fragmentation. Most of the skywalker gibbon population in Myanmar exists outside protected areas. Therefore, the IUCN Red List status of the skywalker gibbon should remain as Endangered.

How context affects transdisciplinary research: insights from Asia, Africa and Latin America - Flurina Schneider; Aymara Llanque-Zonta; Onintsoa Ravaka Andriamihaja; R. Ntsiva N. Andriatsitohaina; Aung Myin Tun; Kiteme Boniface; Johanna Jacobi; Enrico Celio; Clara Léonie Diebold; Laby Patrick; Phokham Latthachack; Jorge Claudio Llopis; et al. (Sustainability Science, 2022)
Transdisciplinary research (TDR) has been developed to generate knowledge that effectively fosters the capabilities of various societal actors to realize sustainability transformations. The development of TDR theories, principles, and methods has been largely governed by researchers from the global North and has reflected their contextual conditions. To enable more context-sensitive TDR framing, we sought to identify which contextual characteristics affect the design and implementation of TDR in six case studies in Asia, Latin America, and Africa, and what this means for TDR as a scientific approach. To this end, we distinguished four TDR process elements and identified several associated context dimensions that appeared to influence them. Our analysis showed that contextual characteristics prevalent in many Southern research sites—such as highly volatile socio-political situations and relatively weak support infrastructure—can make TDR a challenging endeavour. However, we also observed a high degree of variation in the contextual characteristics of our sites in the global South, including regarding group deliberation, research freedom, and dominant perceptions of the appropriate relationship between science, society, and policy. We argue that TDR in these contexts requires pragmatic adaptations as well as more fundamental reflection on underlying epistemological concepts around what it means to conduct “good science”, as certain contextual characteristics may influence core epistemological values of TDR.

Indole and Derivatives Modulate Biofilm Formation and Antibiotic Tolerance of Klebsiella pneumoniae - Thanachaporn Yaikhan; Manatsanan Chuerboon; Natchapol Tippayatham; Nateekarn Atimuttikul; Taiyeebah Nuidate; Mingkwan Yingkajorn; Aung Win Tun; Hansuk Buncherd; Natta Tansila (Indian Journal of Microbiology, 2019)

Genome-wide linkage scan and association study of PARL to the expression of LHON families in Thailand - Nopasak Phasukkijwatana; Bussaraporn Kunhapan; Jim Stankovich; Wanicha L. Chuenkongkaew; Russell Thomson; Timothy Thornton; Melanie Bahlo; Taisei Mushiroda; Yusuke Nakamura; Surakameth Mahasirimongkol; Aung Win Tun; Chatchawan Srisawat; et al. (Human Genetics, 2010)